Temperature explains variable spread rates of the invasive woodwasp Sirex noctilio in the Southern Hemisphere - Lantschner, María Victoria (2014)
The frequency of introductions of non-indigenous forest insects into new habitats is increasing worldwide, often with profoundly adverse consequences on natural and plantation forest ecosystems. Understanding rates and patterns of spread of invasive forest insects is important for predicting when and where these species will expand their geographical range, with the potential to improve mitigation strategies. The woodwasp Sirex noctilio is a damaging invasive forest insect that kills numerous species of Pinus. Despite encountering highly variable eco-climatic conditions, S. noctilio has arrived and established in exotic pine forest production areas throughout the Southern Hemisphere. In this study, we compiled historical records of S. noctilio invasion to compare spread rates among eight contrasting eco-climatic regions in the Southern Hemisphere and to explore how spread rate is predicted by landscape variation in climate, habitat characteristics, and anthropogenic effects. Spread rates for S. noctilio varied considerably among the invaded regions, ranging from 12 to 82 km per year. Among regions, spread rates of S. noctilio increased with increasing mean annual temperature and isothermality. We hypothesize that temperature may directly or indirectly influence S. noctilio population growth and dispersal, thereby influencing spread rates.